Effectiveness of warm-up routine on the ankle injuries prevention in young female basketball players: A randomized controlled trial - Padua, E.; D`Amico, A. G.; Alashram, A.; Campoli, F.; Romagnoli, C.; Lombardo, M.; Quarantelli, M.; Di Pinti, E.; Tonanzi, C.; Annino, G. (Medicina, 2019)
Background and Objectives: Ankle joint is the most common site of injury for basketball athletes. An effective warm-up (WU) is a period of preparatory exercise to improve training performance and reduce sports injuries. Continuous examination of effective WU routines in basketball players is a necessity. The aim of this study was to investigate the effects of general and combined warm up on ankle injury range of motion (ROM) and balance in young female basketball players. Materials and Methods: A sample of 28 young female basketball players were randomly allocated to either global warm up control group (GWU) (n = 11) or combined warm up experimental group (CWU) (n = 17). All participants performed 7-min of run. The CWU group performed a single leg stance barefoot with eyes closed, plank forearm position and triceps sural stretching. Participants in GWU performed walking ball handling and core stability using a Swiss ball. Both WU routines were conducted 3 times per week for 10 weeks. Outcome measurements were the Stabilometric platform and dorsiflexion lunge test. Results: Twenty-eight young female basketball players completed the study. Participants in the experimental group improved significantly in the range of motion (ROM) in right and left ankle and the center of pressure displacement (CoP). The control group did not show any changes in ankle dorsiflexion and a significant reduction in all body balance parameters. Conclusions: An 8-min combined warm-up routine for 10 weeks improves the ankle dorsiflexion ROM and CoP displacement that plays a key role in ankle injuries prevention in basketball players. Further studies are strongly needed to verify our findings.